Chemical vapour deposition synthesis of ultrathin CdTe nanosheet for high performing photodetectors - Lim, Merryl Si Ying (Nanyang Technological University, 2020)
Since the discovery two-dimensional transitional metal dichalcogenides (2D TMDCs), realization techniques of 2D non-layered structure has been highly sort after for its unique physical properties, high flexibility and strong compatibility with silicon substrates [1]. However, realization technique still poses a great challenge as a wurtzite crystal structure in CdTe hinders anisotropic growth. In this study, we demonstrated the controlled synthesis of 2D hexagonal CdTe crystals by exploring the growth parameters through van der Waals epitaxy growth method to obtain uniform thickness and large lateral dimension of crystal. Besides, the optoelectronic properties of CdTe nanosheet was explored for its use as photodetector through various characterisation techniques. The CdTe nanosheet as shown to possess high detectivity, stable photoswitching and ultrafast photoresponse.